Suppose $y=\tanh(z)=\frac{\exp(z) − \exp(−z)}{\exp(z) + \exp(−z)}=\frac{\exp(2z) − 1}{\exp(2z) + 1}$

$$u = \exp(2 z) -1$$ $$v=\exp(2 z)+1$$ $$\frac{\partial y}{\partial z} = \frac{\partial}{\partial z} \left(\frac{u}{v} \right) = \frac{v \frac{\partial u}{\partial a^t_j} - u \frac{\partial v}{\partial z}}{v^2} = \frac{4 \exp (2 z)}{(\exp(2 z)+1)^2}$$

I would be interested in expressing $\frac{\partial y}{ \partial z}$ in function of $y$ directly. I got $$\frac{\partial y}{ \partial z} = \frac{4}{\exp(2z)+1} \left( y + \frac{1}{\exp(2z) +1}\right)$$

Is there a way to simplify that?

  • $\begingroup$ Given your definition of $y$, you have $z = \tanh^{-1}$ where it is defined. Given $\partial y/ \partial z$ as you've calculated, and some trig identities for inverse arctan, can you see how to simplify? $\endgroup$ – Derek Allums Oct 23 at 15:12

Suppose $y=\tanh(z)$ and

$$x=\frac{\partial y}{ \partial z} = \text {sech}^2 (z)$$


$$ x =1 - y^2$$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.